Konflik Antar Kelas dalam Pelaporan Keuangan berdasarkan Perspektif Teori Konflik Karl Marx pada Perusahaan Makanan Siap Saji X, Y, Z di Nusa Tenggara Barat - Dina Amalya Putri (Journal of Innovative and Creativity, 2025)
This study aims to analyze class conflicts in financial reporting practices based on Karl Marx’s conflict theory in three food companies located in West Nusa Tenggara, Indonesia. Marx’s conflict theory serves as the conceptual framework to understand power relations between capital owners (bourgeois class) and workers (proletarian class) within the context of financial reporting, which is not merely technical but also ideological. This research employs a qualitative descriptive approach using a case study method on Companies X, Y, and Z. Data were collected through in-depth interviews with management, accounting staff, and production workers, as well as documentation of internal and external financial reports. Data analysis was conducted through data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results reveal that financial reporting serves as an arena where class conflicts are manifested between capital owners striving to maximize profit and workers seeking better welfare. The conflicts are evident in accounting decisions such as labor cost recognition, inventory valuation, and disclosure policies. Financial reporting is also used as a legitimacy tool to maintain the company’s image among investors and regulators, while issues of distributive justice for workers are often marginalized. Although auditing and corporate governance mechanisms help mitigate conflicts, they still tend to favor the interests of the capital-owning class. This study contributes to the development of critical accounting literature in Indonesia by demonstrating that financial reporting is not entirely neutral but is embedded with power relations and economic interests. Furthermore, the findings provide practical implications for companies to strengthen transparency, ethics, and social justice in their financial reporting practices.